Effect of gingival biotype on orthodontic treatment-inducedperiodontal complications: A systematic review - Reza Amid; Mahdi Kadkhodazadeh; Anahita Moscowchi; Shiva Tavakol Davani; Milad Soleimani; Anahita Dehghani Soltani; Muna Al-Shuhayeb (Tabriz University of Medical Sciences, 2020)
Background. It is crucial to maintain periodontal health in patients undergoing orthodontic treatment. Biotype is a critical factor to be considered in this regard. This systematic review investigated the scientific evidence on the relationship between gingival biotype and marginal periodontal alterations induced by orthodontic interventions. Methods. An electronic search was conducted for pertinent studies in three databases: PubMed, Scopus, and Cochrane up to August 1, 2019 based on a detailed protocol according to the PRISMA statement. The authors also completed a hand search in six dental journals and the bibliographic lists of the relevant studies. Results. Of 1512 citations retrieved through the electronic search, 602 were duplicate entries. By evaluating titles, abstracts, and full texts, eight articles conformed to the inclusion criteria; however, no relevant studies were found through hand searching. The evidence suggested that recession was inversely related with the thickness of the facial margin. These findings were more evident in proclined teeth and patients using fixed appliances. Conclusion. The existing evidence suggests that orthodontic therapy might result in mild detrimental effects on the periodontium, especially in patients with thin biotype. However, due to the limited investigations and their inconsistent methodology, further well-designed prospective studies are necessary.